ZnCl2‐Promoted One‐Pot Three‐Component Synthesis of Multisubstituted Thiazolo[4, 5‐b]pyridines and Thieno[2, 3‐b:4, 5‐b′]dipyridines. Issue 3 (4th December 2014) - Luo, Laichun; Meng, Lanlan; Peng, Yangqiu; Xing, Yongning; Sun, Qi; Ge, Zemei; Li, Runtao
Abstract: A ZnCl2 ‐promoted one‐pot synthesis of multisubstituted thiazolo[4, 5‐ b ]pyridines and thieno[2, 3‐ b :4, 5‐ b′ ]dipyridines from mercaptonitrile salts, α‐bromo ketones and ketones has been developed. This approach involves a tandem SN 2 alkylation/Thorpe–Ziegler cyclization/Friedländer reaction, which allows the creation of two hetero rings and four new bonds in a single operation. The reaction proceeds smoothly under solvent‐free conditions to afford fused pyridines in moderate to good yields. Abstract : A facile ZnCl2 ‐promoted one‐pot three‐component synthesis of thiazolo[4, 5‐ b ]pyridines and thieno[2, 3‐ b :4, 5‐ b′ ]dipyridines is described. This approach involves a tandem SN 2/Thorpe–Ziegler cyclization/Friedländer reaction to give fused pyridines in moderate to good yields.